STRATEGI PROMOSI PENGELOLAAN PARIWISATA INSTAGRAMMABLE DALAM MENINGKATKAN KUNJUNGAN WISATA DI KABUPATEN BANTAENG (Studi Komunikasi Pemasaran Pariwisata Pemandian Alam Batu Doli Kabupaten Bantaeng) - Sabaruddin Machmud; Muhammad Abdi Dzil Ikram (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2022)
This study aims to find out the promotional strategies carried out by the manager of the Batu Doli natural baths tourism area in Bantaeng Regency in increasing millennial tourist visits in the Batu Doli Bantaeng tourist area and to find out the factors that support and hinder the implementation of the promotion strategy for the managers of the Batu Doli natural baths tourism area This research is descriptive qualitative this research lasted for two months and used the methods of observation, interviews, and documentation. The results showed that the promotional strategies used by managers of instagrammable tourist areas are: word of mouth strategy or word of mouth, print media advertising strategies through newspapers, brochures, leaflets, and banners, and strategies for using social media, namely Instagram, blogs, and Facebook. In addition, it also implements other promotional strategies such as the use of employees as promotional communicators and the use of social media accounts. The factors that support the promotion strategy include the beauty of the panorama around the natural baths which are beautiful, cool, and still beautiful, the facilities are quite complete, the location of instagrammable spots is quite a lot and access to tourist locations that are easy, and smooth. Meanwhile, the inhibiting factor is the use of social media Instagram and Facebook belonging to the manager which has not been maximal in promoting the Batu Doli tourist area and the Covid-19 pandemic which is still ongoing today.